TNF-α Induced the Enhanced Apoptosis of Mesenchymal Stem Cells in Ankylosing Spondylitis by Overexpressing TRAIL-R2 - Zhenhua Liu; Liangbin Gao; Peng Wang; Zhongyu Xie; Shuizhong Cen; Yuxi Li; Xiaohua Wu; Le Wang; Hongjun Su; Wen Deng; Shan Wang; Deng Li; et al. (Stem Cells International)
Ankylosing spondylitis (AS) is an autoimmune disease with unknown etiology. Dysregulated mesenchymal stem cells (MSCs) apoptosis may contribute to the pathogenesis of autoimmune diseases. However, apoptosis of MSCs from patients with AS (ASMSCs) has not been investigated yet. The present study aims to assess the apoptosis of bone marrow-derived ASMSCs and to investigate the underlying mechanisms of altered ASMSCs apoptosis. We successfully induced the apoptosis of ASMSCs and MSCs from healthy donors (HDMSCs) using the combination of tumor necrosis factor alpha (TNF-α) and cycloheximide (CHX). We found that ASMSCs treated with TNF-α and CHX showed higher apoptosis levels compared to HDMSCs. During apoptosis, ASMSCs expressed significantly more TRAIL-R2, which activated both the death receptor pathway and mitochondria pathway by increasing the expression of FADD, cleaved caspase-8, cytosolic cytochrome C, and cleaved caspase-3. Inhibiting TRAIL-R2 expression using shRNA eliminated the apoptosis differences between HDMSCs and ASMSCs by partially reducing ASMSCs apoptosis but minimally affecting that of HDMSCs. Furthermore, the expression of FADD, cleaved caspase-8, cytosolic cytochrome C, and cleaved caspase-3 were comparable between HDMSCs and ASMSCs after TRAIL-R2 inhibition. These results indicated that increased TRAIL-R2 expression results in enhanced ASMSCs apoptosis and may contribute to AS pathogenesis.